PENERAPAN METODE PEMBERIAN TUGAS TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DI MADRASAH ALIYAH ALKHAIRAAT FALABISAHAYA - Maani Pora (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The application of the method of giving assignments to student achievement in the subject of Aqeedah Akhlak at Madrasah Aliyah Alkhairaat Falabisahaya. the problem of how to apply and student learning outcomes using the assignment method on learning achievement. The aim of the research is to find out the application of learning outcomes with the assignment method on achievement. This type of research is class action research (classroom action research). action research in the field of education carried out in classroom areas with the aim of improving and enhancing the quality of learning. In short PTK can be defined as an examination of learning activities in the form of an action, which is deliberately raised and occurs in a class together. The implementation of learning in cycle I had no effect on the application of the assignment method with the acquisition of student achievement results or average student abilities. an average of 56.47%, it does not include the completeness of the KKM 75 score set by the school, while in cycle II there is a change in the method of giving assignments in increasing students' cognitive abilities with an average value of 75% and the value includes the completeness of the KKM 75 value determined by the school, so the learning process is has been successful in cycle II, so there is no further learning process action or in cycle III. learning by applying the assignment method to student achievement in the subject of aqidah morals at madrasah aliyah alkhairaat falabisahaya 2021/2022. this can be seen from the student achievement in cycle I by 40% increasing to 80%. in cycle II there was an increase of 40% thus these results met the target set by the researchers of 75%.